Polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin and preparation method thereof
By introducing active carboxylic acid methyl ester groups on the polytetrahydrofuran molecular chain and carrying out transesterification reaction with nanohydroxyethyl cellulose, polytetrahydrofuran grafted nanocellulose is solved, and the problem of poor dispersion of nanocellulose is achieved The toughening and mechanical properties of epoxy resins are improved.
Patent Information
- Application Number
- CN202411760618.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, nanocellulose has poor dispersion in epoxy resin, resulting in poor toughness of epoxy resin and it is difficult to effectively enhance its mechanical properties.
By introducing active carboxylic acid methyl ester groups on the polytetrahydrofuran molecular chain and carrying out transesterification reaction with nanohydroxyethyl cellulose, polytetrahydrofuran grafted nanocellulose is formed, and then combined with epoxy resin to form a network structure. Enhance its mechanical properties.
The good dispersion and toughening effect of nanocellulose in epoxy resin is achieved, and the mechanical properties and fatigue resistance of the epoxy resin are improved.
Smart Images

Figure CN119391138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resins, in particular to a polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin and a preparation method thereof. Background Art
[0002] From wood, bricks and tiles to today's polymer materials, the continuous development of materials is also a major factor driving society. As people's needs continue to change, a variety of materials have emerged. Epoxy resin, due to its excellent mechanical properties, low shrinkage, excellent chemical resistance and electrical insulation, has been widely used in electronics, machinery, construction, coatings and other fields. However, due to its poor toughness, poor fatigue resistance and impact toughness, its application has been further expanded. Therefore, the toughening of epoxy resin has always been a research hotspot.
[0003] Chinese patent CN104194263B "Nano-microcrystalline cellulose composite water-based epoxy resin and its preparation method" discloses a method of directly adding microcrystalline cellulose into epoxy resin to achieve toughening effect. However, due to the large polarity of cellulose and the non-polar material of epoxy resin, there is a problem of dispersibility. Polyether has a flexible molecular chain and can reduce the rigidity of epoxy resin, thereby achieving toughening effect. By combining polyether chain with nanocellulose, the surface polarity of nanocellulose can be reduced, thereby achieving excellent toughening effect on epoxy resin with poor toughness.
[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin and a preparation method thereof, which solves the problems of poor dispersibility of nanocellulose and poor toughness of epoxy resin.
[0005] (II) Technical solution
[0006] To achieve the above object, the present invention provides the following technical solution: A method for preparing polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin comprises the following steps: (1) Dissolve the carboxyl-terminated tetrahydrofuran in dichloromethane, then add thionyl chloride and catalyst N,N-dimethylformamide, react at 20-40°C for 10-18h, and after the reaction is completed, perform vacuum distillation and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) adding chlorinated polytetrahydrofuran to methanol, reacting at 20-40° C. for 12-24 hours, and after the reaction is completed, performing vacuum distillation and washing with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add nano-hydroxyethyl cellulose and dimethylformamide into a reaction container, stir and mix, then add polytetrahydrofuran dicarboxylic acid methyl ester and p-toluenesulfonic acid, raise the temperature to 80-120° C. under a nitrogen atmosphere, stir and react for 3-8 hours, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) The tetrahydrofuran grafted hydroxyethyl cellulose is ultrasonically dispersed in anhydrous ethanol solvent, and then epoxy resin-E51 is added and stirred to mix, and then carboxyl-terminated polytetrahydrofuran and curing agent 4,4-diaminodiphenyl sulfone are added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin.
[0007] Preferably, in step (1), the mass ratio of dichloromethane, carboxyl-terminated tetrahydrofuran, thionyl chloride and catalyst N,N-dimethylformamide is 4000-12000:100:10-30:1-3.
[0008] Preferably, in step (2), the mass ratio of methanol to polytetrahydrofuran chloride is 400-1600:100.
[0009] Preferably, in step (3), the mass ratio of dimethylformamide, nano-hydroxyethyl cellulose, polytetrahydrofuran dicarboxylic acid methyl ester and p-toluenesulfonic acid is 4000-16000:100:60-200:2-4.
[0010] Preferably, in step (4), the mass ratio of anhydrous ethanol, tetrahydrofuran grafted hydroxyethyl cellulose, epoxy resin-E51, carboxyl-terminated polytetrahydrofuran and curing agent 4,4-diaminodiphenyl sulfone is 5-10:0.25-1.2:100:8-15:20-50.
[0011] 3. Beneficial technical effects
[0012] Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects: The polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin comprises carboxylated polytetrahydrofuran with active carboxyl groups introduced at both ends of polytetrahydrofuran by using succinic anhydride, chlorination of the active carboxyl groups of the carboxylated polytetrahydrofuran by using thionyl chloride, and then esterification reaction with methanol, so as to obtain polytetrahydrofuran dicarboxylic acid methyl ester, and transesterification reaction between the active ester group and the hydroxyl group on hydroxyethyl cellulose, so that polytetrahydrofuran is grafted on the surface of nanocellulose, and nanocellulose has a high aspect ratio, excellent performance, high modulus and mechanical strength, and can form a network structure in an epoxy resin matrix, and can play a role in stress transmission in the epoxy resin matrix, so its high mechanical properties can play a role in strengthening and toughening as a reinforcing phase, and the introduction of polytetrahydrofuran molecular chains improves the polarity of nanocellulose, and has the same chain segment with the carboxyl-terminated polytetrahydrofuran participating in curing, so it has better compatibility, can form good dispersibility in the matrix, and better form a network structure, so it also has better toughening effect.
[0013] The polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin introduces active methyl carboxylate groups into the molecular chains of polytetrahydrofuran, thereby introducing polytetrahydrofuran molecular chains onto the surface of nanocellulose. The polytetrahydrofuran molecular chains contain flexible chain segments and thus have a very good toughening effect. The polytetrahydrofuran molecular chains, as toughening phases in the epoxy resin, can effectively enhance the flexibility of the epoxy resin molecular chains after cross-linking and curing, and reduce the rigidity of the epoxy resin. Under the synergistic toughening effect of the nanocellulose and the polytetrahydrofuran, the epoxy resin has more excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The reaction diagram for preparing polytetrahydrofuran acyl chloride; Figure 2 A reaction diagram for preparing polytetrahydrofuran dicarboxylic acid methyl ester; Figure 3 Reaction diagram for preparing polytetrahydrofuran grafted hydroxyethyl cellulose. DETAILED DESCRIPTION
[0015] A method for preparing polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin, characterized in that it comprises the following steps: (1) Dissolve 2 g of carboxyl-terminated tetrahydrofuran in 80-240 g of dichloromethane, then add 0.2-0.6 g of thionyl chloride and 0.02-0.06 g of catalyst N,N-dimethylformamide, react at 20-40° C. for 10-18 h, and after the reaction is completed, perform vacuum distillation and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) Add 0.5 g of polytetrahydrofuran chloride to 2-8 g of methanol, react at 20-40° C. for 12-24 h, and after the reaction is complete, perform vacuum distillation and wash with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add 0.5 g of nano-hydroxyethyl cellulose and 20-80 g of dimethylformamide into a reaction container, stir and mix, then add 0.3-1 g of polytetrahydrofuran dicarboxylic acid methyl ester and 0.01-0.04 g of p-toluenesulfonic acid, raise the temperature to 80-120° C. under a nitrogen atmosphere, stir and react for 3-8 hours, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) Ultrasonic dispersion of 0.5-2.4 g of tetrahydrofuran grafted hydroxyethyl cellulose in 10-20 g of anhydrous ethanol solvent, followed by addition of 200 g of epoxy resin-E51, stirring and mixing, followed by addition of 16-30 g of carboxyl-terminated polytetrahydrofuran and 40-100 g of curing agent 4,4-diaminodiphenyl sulfone, to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin. Example 1
[0016] (1) Dissolve 2 g of carboxyl-terminated tetrahydrofuran in 80 g of dichloromethane, then add 0.2 g of thionyl chloride and 0.02 g of catalyst N,N-dimethylformamide, react at 20 ° C for 10 h, and after the reaction is completed, distill under reduced pressure and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) Add 0.5 g of polytetrahydrofuran chloride to 2 g of methanol, react at 20° C. for 12 h, and after the reaction is complete, perform vacuum distillation and wash with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add 0.5 g of nano-hydroxyethyl cellulose and 20 g of dimethylformamide into a reaction container, stir and mix, then add 0.3 g of polytetrahydrofuran dicarboxylic acid methyl ester and 0.01 g of p-toluenesulfonic acid, raise the temperature to 80°C under a nitrogen atmosphere, stir and react for 3 h, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) 0.5 g of tetrahydrofuran grafted hydroxyethyl cellulose was ultrasonically dispersed in 10 g of anhydrous ethanol solvent, and then 200 g of epoxy resin-E51 was added and stirred to mix. Then, 16 g of carboxyl-terminated polytetrahydrofuran and 40 g of curing agent 4,4-diaminodiphenyl sulfone were added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin. Example 2
[0017] (1) Dissolve 2 g of carboxyl-terminated tetrahydrofuran in 100 g of dichloromethane, then add 0.3 g of thionyl chloride and 0.03 g of catalyst N,N-dimethylformamide, react at 20 °C for 12 h, and after the reaction is completed, distill under reduced pressure and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) Add 0.5 g of polytetrahydrofuran chloride to 3 g of methanol, react at 20° C. for 14 h, and after the reaction is complete, perform vacuum distillation and wash with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add 0.5 g of nano-hydroxyethyl cellulose and 30 g of dimethylformamide into a reaction container, stir and mix, then add 0.5 g of polytetrahydrofuran dicarboxylic acid methyl ester and 0.02 g of p-toluenesulfonic acid, raise the temperature to 90°C under a nitrogen atmosphere, stir and react for 4 h, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) 0.9 g of tetrahydrofuran grafted hydroxyethyl cellulose was ultrasonically dispersed in 12 g of anhydrous ethanol solvent, and then 200 g of epoxy resin-E51 was added and stirred to mix. Then, 20 g of carboxyl-terminated polytetrahydrofuran and 50 g of curing agent 4,4-diaminodiphenyl sulfone were added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin. Example 3
[0018] (1) Dissolve 2 g of carboxyl-terminated tetrahydrofuran in 100 g of dichloromethane, then add 0.3 g of thionyl chloride and 0.03 g of catalyst N,N-dimethylformamide, react at 30 ° C for 14 h, and after the reaction is completed, distill under reduced pressure and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) Add 0.5 g of polytetrahydrofuran chloride to 5 g of methanol, react at 30° C. for 16 h, and after the reaction is completed, perform vacuum distillation and wash with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add 0.5 g of nano-hydroxyethyl cellulose and 50 g of dimethylformamide into a reaction container, stir and mix, then add 0.6 g of polytetrahydrofuran dicarboxylic acid methyl ester and 0.03 g of p-toluenesulfonic acid, raise the temperature to 100 ° C under a nitrogen atmosphere, stir and react for 5 h, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) 1.8 g of tetrahydrofuran grafted hydroxyethyl cellulose was ultrasonically dispersed in 15 g of anhydrous ethanol solvent, and then 200 g of epoxy resin-E51 was added and stirred to mix. Then, 24 g of carboxyl-terminated polytetrahydrofuran and 60 g of curing agent 4,4-diaminodiphenyl sulfone were added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin. Example 4
[0019] (1) Dissolve 2 g of carboxyl-terminated tetrahydrofuran in 200 g of dichloromethane, then add 0.5 g of thionyl chloride and 0.05 g of catalyst N,N-dimethylformamide, react at 35 °C for 16 h, and after the reaction is completed, distill under reduced pressure and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) Add 0.5 g of chlorinated polytetrahydrofuran to 7 g of methanol, react at 30° C. for 20 h, and after the reaction is complete, perform vacuum distillation and wash with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add 0.5 g of nano-hydroxyethyl cellulose and 70 g of dimethylformamide into a reaction container, stir and mix, then add 0.9 g of polytetrahydrofuran dicarboxylic acid methyl ester and 0.03 g of p-toluenesulfonic acid, heat to 110° C. under nitrogen atmosphere, stir and react for 7 h, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) 2.1 g of tetrahydrofuran grafted hydroxyethyl cellulose was ultrasonically dispersed in 18 g of anhydrous ethanol solvent, and then 200 g of epoxy resin-E51 was added and stirred to mix. Then, 27 g of carboxyl-terminated polytetrahydrofuran and 80 g of curing agent 4,4-diaminodiphenyl sulfone were added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin. Example 5
[0020] (1) Dissolve 2 g of carboxyl-terminated tetrahydrofuran in 240 g of dichloromethane, then add 0.6 g of thionyl chloride and 0.06 g of catalyst N,N-dimethylformamide, react at 40 ° C for 18 h, and after the reaction is completed, distill under reduced pressure and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) Add 0.5 g of polytetrahydrofuran chloride to 8 g of methanol, react at 40° C. for 24 h, and after the reaction is complete, perform vacuum distillation and wash with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add 0.5 g of nano-hydroxyethyl cellulose and 80 g of dimethylformamide into a reaction container, stir and mix, then add 1 g of polytetrahydrofuran dicarboxylic acid methyl ester and 0.04 g of p-toluenesulfonic acid, heat to 120° C. under nitrogen atmosphere, stir and react for 8 h, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) 2.4 g of tetrahydrofuran grafted hydroxyethyl cellulose was ultrasonically dispersed in 20 g of anhydrous ethanol solvent, and then 200 g of epoxy resin-E51 was added and stirred to mix, and then 30 g of carboxyl-terminated polytetrahydrofuran and 100 g of curing agent 4,4-diaminodiphenyl sulfone were added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin.
[0021] Comparative Example 1 (1) 0.8 g of hydroxyethyl cellulose was ultrasonically dispersed in 16 g of anhydrous ethanol solvent, and then 200 g of epoxy resin-E51 was added and stirred to mix, and then 27 g of carboxyl-terminated polytetrahydrofuran and 60 g of curing agent 4,4-diaminodiphenyl sulfone were added to obtain nanocellulose toughened and reinforced epoxy resin.
[0022] The epoxy resins prepared in Examples 1-5 and Comparative Example 1 are compared as follows: After curing, the epoxy resins prepared in the embodiment and the comparative example were respectively made into standard impact specimens, and the impact strength was tested using a CBS-50J digital display simply supported beam impact tester, and the test standard was GB / T 1843-2008.
[0023] project Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Notched impact strength (MPa) 24.8 28.0 30.7 27.7 24.1 19.5
Claims
1. A polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin, characterized in that: The method for preparing a polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin comprises the following steps: (1) Dissolve the carboxyl-terminated tetrahydrofuran in dichloromethane, then add thionyl chloride and catalyst N,N-dimethylformamide, react at 20-40°C for 10-18h, and after the reaction is completed, perform vacuum distillation and wash with deionized water to obtain chlorinated polytetrahydrofuran; (2) adding chlorinated polytetrahydrofuran to methanol, reacting at 20-40° C. for 12-24 hours, and after the reaction is completed, performing vacuum distillation and washing with deionized water to obtain polytetrahydrofuran dicarboxylic acid methyl ester; (3) Add nano-hydroxyethyl cellulose and dimethylformamide into a reaction container, stir and mix, then add polytetrahydrofuran dicarboxylic acid methyl ester and p-toluenesulfonic acid, raise the temperature to 80-120° C. under a nitrogen atmosphere, stir and react for 3-8 hours, wash with anhydrous ethanol and deionized water, and vacuum dry to obtain polytetrahydrofuran grafted hydroxyethyl cellulose; (4) The tetrahydrofuran grafted hydroxyethyl cellulose is ultrasonically dispersed in anhydrous ethanol solvent, and then epoxy resin-E51 is added and stirred to mix, and then carboxyl-terminated polytetrahydrofuran and curing agent 4,4-diaminodiphenyl sulfone are added to obtain polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin.
2. A polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin according to claim 1, characterized in that: In the step (1), the mass ratio of dichloromethane, carboxyl-terminated tetrahydrofuran, dichlorothionyl and catalyst N,N-dimethylformamide is 4000-12000:100:10-30:1-3.
3. A polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin according to claim 1, characterized in that: In the step (2), the mass ratio of methanol to polytetrahydrofuran chloride is 400-1600:
100.
4. A polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin according to claim 1, characterized in that: In the step (3), the mass ratio of dimethylformamide, nano-hydroxyethyl cellulose, polytetrahydrofuran dicarboxylic acid methyl ester and p-toluenesulfonic acid is 4000-16000:100:60-200:2-4.
5. The polytetrahydrofuran-nanocellulose toughened and reinforced epoxy resin according to claim 1, characterized in that: In the step (4), the mass ratio of anhydrous ethanol, tetrahydrofuran grafted hydroxyethyl cellulose, epoxy resin-E51, carboxyl-terminated polytetrahydrofuran and curing agent 4,4-diaminodiphenyl sulfone is 5-10:0.25-1.2:100:8-15:20-50.
Citation Information
Patent Citations
Nano-microcrystalline cellulose composite water-based epoxy resin and preparation method thereof
CN104194263B
Preparation method of hyperbranched polyester graft modified sisal fiber cellulose microcrystal
CN103951830A
Organic nano magnetic core material with high winding ratio and high permeability for switching power supply transformer and preparation method of material
CN106847459A
Composite for cellulose fiber dispersion and cellulose fiber composition
US20210403683A1
Cited By
Large-current aluminum alloy conductor-based power cable with long service life
CN121215347A
Environment-friendly nano solubilizer for oil field and preparation method of environment-friendly nano solubilizer
CN121759188A